Beberapa Aspek Hukum dalam Perjanjian Ekstradisi Antara Indonesia dan Singapura - Deli Waryenti (UNIB Press, 2022)
The extradition treaty between Indonesia which took such a long time contained several legal aspects such as retro-active principles, non-legality, non-change of citizenship, progressive and flexible principles according to the times. However, all legal aspects contained in the extradition treaty which are actually contrary to the law in general, are not necessarily able to return the corruptors who fled to Singapore for several reasons, namely: the agreement that follows the extradition treaty (defense agreement and FIR) is detrimental to Indonesia, the grace period has expired. 18 years is not enough because the corruptors carried out the corruption above 18 years ago, and the corruptors are estimated to have left Singapore and went to other countries that do not have an extradition treaty with Indonesia. Keywords: Extradition; International; Treaty.